2021
DOI: 10.1016/j.ultsonch.2021.105667
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical recovery of uranium from nanosilica-based sorbent and its biohybrid

Abstract: Highlights Intensified reprocessing of silica-based microstructures and its biohybrid. Parametric study of reprocessing of microstructures. Kinetics of uranium recovery from substrates. Morphology and recyclability study of the substrates after sonication and uranium recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“…The kinetic data showed that the ceria recovery followed a surface reaction control mechanism, in contrast to the ash diffusion control mechanism reported earlier for uranium [4] and yttrium [5] , [40] . Fig.…”
Section: Resultscontrasting
confidence: 90%
“…The kinetic data showed that the ceria recovery followed a surface reaction control mechanism, in contrast to the ash diffusion control mechanism reported earlier for uranium [4] and yttrium [5] , [40] . Fig.…”
Section: Resultscontrasting
confidence: 90%
“…Synthesized doughnut shaped microstructures have shown more than 85 ± 2% of total uranium uptake in just 10 min and 92% uptake in 120 min. However, while recovery, it was observed that the adsorption capacity of microstructures was reduced from 92% to 67% [73]. This may be due to the changes in morphology and loss of adsorption sites after acid and ultrasonics treatment.…”
Section: Remediation Of Heavy Metals and Bioprocessingmentioning
confidence: 97%
“…In our laboratory, we have synthesized various spray dried microstructures using silica nanoparticles and biomolecules through the process of spray drying [71,72]. Microstructures of silica NPs and Streptococcus lactis (S. lactis) cells were prepared, applied for removal of uranium from aqueous solution and recovery of adsorbed uranium were also studied [27,73]. It was observed that various morphologies can be achieved by varying the physicochemical parameters of the spray drying process.…”
Section: Remediation Of Heavy Metals and Bioprocessingmentioning
confidence: 99%
“…On the other hand, uranium leaching into 6-8 M HNO3 solutions from uranium-impregnated spherical graphite tokens with a diameter of ca. 15 mm is accelerated on 7-15% only under the effect of 20-40 kHz ultrasound [66]. However, at [HNO3] = 12 M and 20 kHz ultrasound the significant loss of uranium is observed due to the graphite erosion and formation of graphitic dust.…”
Section: Sonochemical Reactions Of Actinides In Heterogeneous Systemsmentioning
confidence: 98%